(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
This research is based on problems related to Covid-19 which is currently the center of world attention, which has a major impact on human life and also nature both on land and at sea, one of which is the coral reef ecosystem. In general, the damage to coral reefs is due to the high activity of the community and tourists in the coral reef ecosystem. Based on this explanation, the purpose of this study is to analyze the Impact of Covid-19 on the Coral Reef Ecosystem in the Banda Sea. The method used in this research is observation, data collection from several literatures in the field of fisheries, and interviews. Based on data obtained at several locations in the Banda Islands, the condition of the coral reefs seems to be improving, with the highest coral cover in TWP Pulau Ay - Pulau Rhun at 53.2%, Banda Islands at 41%. The highest HCL cover 75% (EXCELLENT) was the Leaning Tree with a depth of 10 meters and the island of Karaka with a depth of 3 meters. Meanwhile, the locations with the lowest average HCL cover were South Volcano (11.3%), Batu Holland (23.5%) and Hatta Island (24.5%). Based on the results of the analysis, it can be seen that the percentage of coral cover in the Banda islands has increased during the Covid-19 pandemic. It was concluded that the COVID-19 pandemic had a positive impact on coral reef ecosystems in the Banda islands.